(untitled) (Research, Society and Development, 2021)
Higher education promotes an environment full of change for academics. This study aims to assess the perception of happiness and well-being among students from a private higher education institution in the State of Tocantins, Brazil. This is an exploratory and descriptive research, with qualiquantitative analysis, which sought to better understand the perception of Happiness and Well-being, the research consists of 104 academics from the Santa Catarina Educational Institute/ Faculdade Guaraí- IESC/FAG. The sample consisted of 61% female students, 35% male and 5% declared themselves to be of the other sex, aged between < 20 and > 30 years. The results showed that most students had a good quality of life, indicating an association with academic performance and success, which are related aspects. This shows that institutions must carry out guaranteed interference, mainly in the characteristics of the courses and their graduates, and reinforce the importance of pedagogical projects with psychosocial development.